2008
DOI: 10.1097/hjh.0b013e3283060c5c
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous soluble receptor for advanced glycation endproducts is increased in preeclampsia

Abstract: We showed that maternal esRAGE concentrations are significantly increased in patients with preeclampsia during pregnancy. Here, insulin sensitivity and inflammatory status independently predict serum esRAGE levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…Our findings of lower sRAGE in pregnant women with T1DM who subsequently developed PE (compared with those who remained normotensive) are novel and clearly different from those found in previous cross-sectional studies of pregnant women without diabetes. [23][24][25][26]28 The latter showed elevated sRAGE and/or AGE associated with the presence of PE. They do not provide data on the levels of sRAGE in early pregnancy, nor do they address levels in the presence of T1DM.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our findings of lower sRAGE in pregnant women with T1DM who subsequently developed PE (compared with those who remained normotensive) are novel and clearly different from those found in previous cross-sectional studies of pregnant women without diabetes. [23][24][25][26]28 The latter showed elevated sRAGE and/or AGE associated with the presence of PE. They do not provide data on the levels of sRAGE in early pregnancy, nor do they address levels in the presence of T1DM.…”
Section: Discussionmentioning
confidence: 94%
“…21,22 Several cross-sectional studies in pregnant women without diabetes have shown elevated RAGE and AGEs to be associated with vascular dysfunction in PE versus controls. [23][24][25][26][27][28] However, these studies have not addressed whether an altered sRAGE-AGE system precedes or is a consequence of PE. Furthermore, no data have been reported on the causal associations of sRAGE and AGEs with PE in T1DM, a condition associated with a four-fold increase in PE.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence concerning maternal adiponectin concentrations in the presence of preeclampsia is inconsistent: higher [41, 58, 59, 70, 92, 112, 113, 116, 130, 159], lower [31, 33, 34, 63, 125], and similar adiponectin concentrations [119, 120, 145, 160] have been reported in patients with preeclampsia compared to normal pregnant women. This alleged inconsistency may be due to differences in the study population characteristics, definitions of preeclampsia (mild vs. severe, early vs. late onset), sample size or methods by which adiponectin concentrations were determined.…”
Section: Discussionmentioning
confidence: 99%
“…An increase toward mid-pregnancy and a decrease thereafter or inversely, a mid-gestational trough has been described [23] . In women with PE, the scarcity of data does not allow a sound conclusion regarding its variation, but sRAGE levels appear to be increased [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, further studies are needed to provide clarification on these issues. Another study showed that the increasing levels of esRAGE in women with PE did not persist at 6 months after delivery [35] . Therefore, we support the view that the variations in sRAGE levels in both maternal blood and umbilical cord blood are rather an effect of PE than a cause of the disease.…”
Section: Discussionmentioning
confidence: 99%